1989
DOI: 10.1002/gcc.2870010206
|View full text |Cite
|
Sign up to set email alerts
|

Isochromosome 17q in primitive neuroectodermal tumors of the central nervous system

Abstract: We have prepared karyotypes from 22 primitive neuroectodermal tumors (PNETs) from pediatric patients ranging in age from 10 months to 16 years. Twenty-one cases were newly diagnosed, primary, posterior fossa tumors. One case was a recurrent tumor in a patient previously treated with radiation. Cytogenetic results were obtained from direct preparations and/or short-term (1-10 day) culture. Three tumors had apparently normal karyotypes. Nineteen tumors demonstrated numerical and/or structural abnormalities. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(80 citation statements)
references
References 18 publications
6
72
1
1
Order By: Relevance
“…The findings of gain of 17q with reciprocal loss of 17p in 26% of our cases of medulloblastoma are consistent with cytogenetic reports (Biegel et al, 1989;Bigner et al, 1997), with two smaller series of cases studied using CGH (Schütz et al, 1996;Reardon et al, 1997), and with findings of LOH on 17p (Cogen et al, 1990;Blaeker et al, 1996). The relative importance of 17p loss and 17q gain remains unclear.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of gain of 17q with reciprocal loss of 17p in 26% of our cases of medulloblastoma are consistent with cytogenetic reports (Biegel et al, 1989;Bigner et al, 1997), with two smaller series of cases studied using CGH (Schütz et al, 1996;Reardon et al, 1997), and with findings of LOH on 17p (Cogen et al, 1990;Blaeker et al, 1996). The relative importance of 17p loss and 17q gain remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Cytogenetic studies of medulloblastoma and other PNETs have identified several non-random chromosomal aberrations in a high proportion of cases (Biegel et al, 1989;Bhattachajee et al, 1997;Bigner et al, 1997). Of these, isochromosome 17q [i(17q)] is the most common, occurring in a third of cases overall (Mertens et al, 1994).…”
mentioning
confidence: 99%
“…Numerous studies have described genetic rearrangements, for example, losses, gains and mutations of various chromosomal regions in medulloblastomas. Losses on chromosome 17p through i(17q) (Biegel et al, 1989) or unbalanced translocation and loss of heterozygosity (LOH) on chromosome 1q, 8p, 10q, 11, 16q and 17p was frequently found Kraus et al, 1996;Reardon et al, 1997). For many of these regions the target is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The adult tumor is said to occur more often in the cerebellar hemispheres than the vermis and is more often desmoplastic in histology (Aragones et al, 1994;Frost et al, 1995;Prados et al, 1995). Karyotypic analysis of medulloblastoma nds frequent structural abnormalities, with chromosome 17 the most frequently affected (Biegel et al, 1989).…”
mentioning
confidence: 99%